Harmonizing Data Privacy Frameworks in Artificial Intelligence: Comparative Insights from Asia and Europe - Laksito, Joni; Pratiwi, Berliant; Ariani , Widya (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The rapid adoption of artificial intelligence (AI) has significantly transformed various sectors, such as healthcare, finance, and transportation. However, it also raises critical challenges regarding data privacy, particularly in large-scale data collection and processing. This study explores the differences and similarities in data privacy regulations governing AI between Europe and Asia, focusing on the General Data Protection Regulation (GDPR) in Europe and various regulations such as the Act on the Protection of Personal Information (APPI) in Japan and the Personal Information Protection Law (PIPL) in China. Using a qualitative approach with comparative legal analysis, this research evaluates the principles, flexibility, and practical implications of these regulations for fostering responsible AI development. The findings reveal that while GDPR emphasizes individual protection through transparency and explicit consent, Asia adopts a more flexible approach tailored to national needs, balancing innovation and privacy. However, challenges such as harmonizing cross-border data policies and adapting regulations to rapidly evolving technologies persist. This study contributes to the discourse by highlighting the implications of these regulatory differences for global cooperation and offering strategic recommendations for policymakers and industries. In a globalized digital landscape, aligning legal frameworks is essential not only to protect individual rights but also to build public trust in emerging AI technologies.